2020
DOI: 10.3390/antiox9090782
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Esters: Octinoxate Substitutes Combining Suitable UV Protection and Antioxidant Activity

Abstract: In 2021, Hawaii will permanently ban the use and sale of octinoxate-based sunscreens as studies have shown serious impacts of such UV filters on the coral reef. This ban, which could be generalized to other countries, highlights the extreme need to offer alternative UV filters that are not only effective in terms of sun protection, but also healthy with regards to human health and the environment. In this context, a wide library of p-hydroxycinnamic esters deriving from naturally occurring sinapic acid has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Other synthetic SinEs are of great interest with regard to their photophysical and biological properties (Dean et al, 2014;Baker et al, 2018;Peyrot et al, 2020a). Most SinEs are obtained via Knoevenagel-Doebner condensations (Baker et al, 2018;Peyrot et al, 2020a). The is more advantageous than direct acid-catalyzed esterification of SinA, as it enables access to a larger range of SinEs while remaining simple and ecologically attractive (e.g., no protection/deprotection sequences).…”
Section: Other Sinapoyl Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other synthetic SinEs are of great interest with regard to their photophysical and biological properties (Dean et al, 2014;Baker et al, 2018;Peyrot et al, 2020a). Most SinEs are obtained via Knoevenagel-Doebner condensations (Baker et al, 2018;Peyrot et al, 2020a). The is more advantageous than direct acid-catalyzed esterification of SinA, as it enables access to a larger range of SinEs while remaining simple and ecologically attractive (e.g., no protection/deprotection sequences).…”
Section: Other Sinapoyl Estersmentioning
confidence: 99%
“…As prominent p-hydroxycinnamic acid, SinA and its derivatives also exhibit high photo-stability and UV-absorption (Dean et al, 2014;Horbury et al, 2019;Peyrot et al, 2020a). The photophysical properties of numerous synthetic SinEs were recently studied by Peyrot et al (Peyrot et al, 2020a;Peyrot et al, 2020b) who have reported comparable, or even better, photo-activities of these synthetic p-hydroxycinnamic acids than octinoxate (a conventional fossil-based UV-filter reagent) in term of UV absorption and photostability.…”
Section: Uv-filter Activitiesmentioning
confidence: 99%
“…The cosmeceutical applications result from the antioxidant activity and anti-tyrosinase, anti-collagenase, anti-hyaluronidase, photoprotective, anti-inflammatory, and antimicrobial activity [47,49]. The UV-filtering and anti-radical properties of sinapate derivatives suggest an interesting potential application of sinapic acid in sunscreen formulations, replacing currently-used synthetic UV-filtering agents, shown to have a negative impact on the environment and human health [50]. This potential high-value application of sinapic acid opens new perspectives to the market segment of environmentally-friendly cosmetic products.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In addition, Arabidopsis plants overexpressing OsBISCPL1 also showed an increased tolerance to oxidative stress, indicating that the gene may be involved in the regulation of defense responses against oxidative stress and pathogen infection [ 28 ]. In Arabidopsis thaliana , SNG1 and SNG2 act as acyltransferases and participate in the biosynthesis of sinapic acid esters, which has ultraviolet protection and antioxidant effects [ 29 32 ]. In addition, when respond to a variety of abiotic stresses, including drought, salinity, light, nitrogen and phosphorus deficiency, and suboptimal or supra-optimal temperatures, anthocyanins are also commonly induced in plants [ 33 39 ].…”
Section: Introductionmentioning
confidence: 99%